2018
DOI: 10.1521/aeap.2018.30.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use, Mental Health, HIV Testing, and Sexual Risk Behavior Among Men Who Have Sex With Men in the State of Maharashtra, India

Abstract: Among 433 men who have sex with men in Maharashtra, India who completed an online survey, 23% reported hazardous drinking, 12% illicit substance, and 9% polysubstance use. The overall prevalence of depression and intimate partner violence (IPV) were 58% and 56%, respectively. Participants engaging in hazardous drinking had more sexual partners and were less likely to be married to women. Participants reporting illicit substance use or polysubstance use were more likely to have been out, had more sexual partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In addition to illness representations, mental health may be particularly salient for HCV testing. Associations between mental health problems (ie, depressive and anxiety symptoms) have been shown to be barriers to prevention of HIV and STIs among MSM 24…”
Section: Introductionmentioning
confidence: 99%
“…In addition to illness representations, mental health may be particularly salient for HCV testing. Associations between mental health problems (ie, depressive and anxiety symptoms) have been shown to be barriers to prevention of HIV and STIs among MSM 24…”
Section: Introductionmentioning
confidence: 99%
“…In Gatzweiler and Baumüller’s (2014) terms, this can lead to social marginality that becomes economic, educational, and political, as people may be ostracized from their families and communities (Dasgupta & Gokulsing, 2013). These individuals may feel marginalized both from other LGBTQ+ people as well as their families and the broader population, leading to isolation, shame and risky behavior (Banik et al, 2019; Chakrapani et al, 2017; Ekstrand et al, 2017; Wilkerson et al, 2018).…”
mentioning
confidence: 99%
“…38, 42, 44 One study reported higher risk for substance use amongst those who were out, and also those who had more sexual partners, or had experiences of intimate partner violence. 46…”
Section: Resultsmentioning
confidence: 99%
“…38,42,44 One study reported higher risk for substance use amongst those who were out, and also those who had more sexual partners, or had experiences of intimate partner violence. 46 Social support satisfaction was associated with lower risk of anxiety, depression, and suicidal ideation. 41 Higher self-esteem was associated with lower risk for depression and suicide.…”
Section: Risk and Protective Factors For Mental Health Conditionsmentioning
confidence: 96%
See 1 more Smart Citation